NORMELE UNIUNII EUROPENE PRIVIND MUNCA PRIN AGENT DE MUNCĂ TEMPORARĂ - Mara Ioan (EIRP Proceedings, 2008)
At a European Union level, work by temporary work agents is not regulated. Still, there aretwo directives which refer to it: Directive 91/383/CEE as a supplement to the measures aimed at encouragingthe bettering of health and security within the wok place for the workers with a time-bound work contract ortemporary, and Directive 96/71 regarding transferring of workers in the case of services offered.